Intertextuality of the headline complexes in mediatexts - Kalenych, Volodymyr (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article deals with the functional-stylistic and communicative-pragmatic features of intertextuality in headline complexes and their compositional role in the modern mediatexts (based on the publications of the information-analytical weekly "Dzerkalo tyzhnya"). Intertext is a cognitive-communicative category and a text-forming element, which implements the author's idea. The intertextual techniques are used in the main headings, subheadings, inner headings, epigraphs, leads. They serve to pay attention to the problem, to express the attitude and leading opinion of the publication, to draw parallels, comparisons, analogies between the intertext and mediadiscourse. These components concisely set the topic, reveal the idea, concept or create a subtext, adjust the reader to the appropriate perception of the publication. The main intertextual means in the headline complexes are proverbs and sayings, winged expressions, quotes, titles of literary works and films, their characters, etc. Analysis of mediatexts has shown that they are included in the headlines in a transformed form more often, the structure and semantics of the original intertext are changed. Allusions as the intertextual methods of imagery and expressiveness in the media evoke metaphorical associations with hinting at well-known social-historical or literary facts, events, phrases, characters of other texts. The elements of the mediatext (epigraph, lead, summary etc) complement and reveal intertextual headings. The epigraph is an optional element of the headline complex of mediatexts and a laconic intertextual technique. Before the text an accurate quotation helps to understand the concept and problem-thematic parameters of the mediatext. The intertextuality in the headline complex provokes emotional and semantic associations, they facilitate the perception of the text, but do not reveal the topic and content of the article, attract the interest of the reader only pragmatically. The intertextual means contribute to language economy and at the same time expand the semantic perspective of media headline, successfully implement their advertising function – to interest, to intrigue, to influence the subconscious referring to well-known texts and images. The language game expresses the headline complex aesthetically, attracts the reader to a productive knowing the publication, analytical understanding of reality.
Keywords: intertextuality, headline complex, headline, epigraph, quotation, allusion, composition, mediatext.